Development of the Indian Telecommunication Sector throughout Last Decade: A Tale about Merits and Demerits of Telecom Law and Competition Law in India (Law, State and Telecommunications Review, 2024)
[Purpose] During the post-liberalization era, the Indian legal system introduced multiple laws with the objective of safeguarding the interests of Indian consumers and fostering equitable competition within the telecommunications sector. Notably, the Indian legal system has demonstrated a significant commitment to the resolution of telecommunications-related disputes, exemplified by the enactment of the Telecom Regulatory Authority of India (TRAI) Act in 1997 and the Competition Act in 2002. Both legislative measures were designed to advance the cause of fair competition in the telecommunications industry. The primary purpose of this article is to conduct an examination of whether the objectives set forth by these two Acts have been effectively realized over the past decade (2012-2021). Additionally, this article will undertake a comparative analysis of these Acts in relation to legal frameworks in other countries beyond India.[Methodology] The foundational methodology employed in this research centers on the analysis of cases adjudicated by both the Telecom Regulatory Authority and the Competition Regulatory Authority in India, particularly in instances involving disputes within the telecommunications sector. This article offers a concise data analysis concerning the evolution of the Indian telecommunications market over the past decade (2012-2021). The primary aim is to undertake a critical evaluation of the effectiveness of the Acts in place for the preservation of fair competition within this industry.[Findings] Based on the legal analysis, this article argues that there is an unresolved territorial dispute between the Telecom Regulatory Authority of India (TRAI) Under section 3 of the Telecom Regulatory Authority of India Act, 1997, the Indian government established the regulatory agency to oversees the telecommunications industry in India and the Competition Act, 2002 establishes the Competition Commission of India being primary national competition regulator in India. It is an official department of the Ministry of Corporate Affairs tasked with upholding the Competition. The findings also suggest that the Government of India should overhaul its institutional framework in order to insert the “collective dominance” concept in the Competition Act. This concept/amendment was about to be passed in the India Congress by the United Progressive Alliance (UPA) Government in 2014. However, it failed due to dissolution of the Lok Sabha, the lower house of India’s bicameral Parliament. Consequently, numerous disputes and concerns remained unresolved. Lastly, Reliance JIO Infocomm Limited is a Public Company that was established on February 15, 2007, is categorized as a Non-Government Company, and is registered with the Registrar of Companies in Mumbai, India. It applied a “zero pricing” strategy which created market distortion which reduced most of the rivals from the telecom market. This kind of strategy was previously ordered void in the NSE[1] case but the same was allowed to the JIO on the premises that it was a new entrant and not dominant. The Competition laws mostly address “predatory pricing”, however, in the matter of “penetrative pricing” they have remained silent. The “penetrative pricing” is allowed for the promotion, but the benchmark of promotion has not yet been regulated. [1] NSE National Stock Exchange